Translating Russian Literature in the Global Context - Muireann Maguire; Cathy McAteer (Open Book Publishers, 2024)
Translating Russian Literature in the Global Context examines the translation and reception of Russian literature as a world-wide process. This volume aims to provoke new debate about the continued currency of Russian literature as symbolic capital for international readers, in particular for nations seeking to create or consolidate cultural and political leverage in the so-called ‘World Republic of Letters'. It also seeks to examine and contrast the mechanisms of the translation and uses of Russian literature across the globe. This collection presents academic essays, grouped according to geographical location, by thirty-seven international scholars. Collectively, their expertise encompasses the global reception of Russian literature in Europe, the Former Soviet Republics, Africa, the Americas, and Asia. Their scholarship concentrates on two fundamental research areas: firstly, constructing a historical survey of the translation, publication, distribution and reception of Russian literature, or of one or more specific Russophone authors, in a given nation, language, or region; and secondly, outlining a socio-cultural microhistory of how a specific, highly influential local writer, genre, or literary group within the target culture has translated, transmitted, or adapted aspects of Russian literature in their own literary production. Each section is prefaced with a short essay by the co-editors, surveying the history of the reception of Russian literature in the given region. Considered as a whole, these chapters offer a wholly new overview of the extent and intercultural penetration of Russian and Soviet literary soft power during the twentieth and twenty-first centuries. This volume will open up Slavonic Translation Studies for the general reader, the student of Comparative Literature, and the academic scholar alike.